PEMANFAATAN DRONE DJI PHANTOM 4 PRO DAN APLIKASI SIG (ArcGIS) UNTUK IDENTIFIKASI BATAS ADMINISTRASI WILAYAH DI KEC. KUANTAN TENGAH KABUPATEN KUANTAN SINGINGI - Rikki Afrizal; Riki Ruspianda; Retni Pratiwi (JURNAL PERANGKAT LUNAK, 2022)
Utilization of Drones, also known as UAV (unmanned aerial vehicles), is currently widely used to evaluate changes in land use, disasters, monitoring regional spatial planning, identifying regional changes, environmental changes, and mapping regional administrative boundaries. Administrative boundaries are boundaries or imaginary lines that are only found on maps and not on the ground in accordance with applicable legal provisions but are only marked with an object that can be recognized by the user, for example stakes, gates, walls, and so on. This study aims to provide information about the actual boundaries of the area according to the current situation and conditions by testing the level of accuracy of Drone photos and comparing them in the field. This study uses a survey method and manual interpretation. This research was conducted in parts of the administrative area of Kuantan Tengah District, namely Pasar Taluk Village and Simpang Tiga Village. The selection of the study area was due to several factors, such as the area's high population density, fast development growth, and being located in the center of Teluk Kuantan city. Aerial photos produced by the Phantom 4 Pro Drone in this study have a spatial resolution of 0.5 meters, thus providing clear and detailed object appearances that can be identified using the ArcGIS application in the Pasar Taluk Village and Simpang Tiga Village areas. Keywords: Drone, land, boundary, region, identification